Detection of Antibacterial Effects of Various Fruit Species on Motile Aeromonas species - Ulutas, Aycan; Qorun, Jale (Acta Aquatica: Aquatic Sciences Journal, 2021)
The aim of this study is to determine the antimicrobial effects of extracts prepared from orange (Citrus sinensis L.), lemon (C. limon L.) and pomegranate (Punica granatum L.) peels on motile Aeromonas species including Aeromonas hydrophila, A. caviae and A. allosaccharophila using disc diffusion and broth dilution techniques. In addition, the antibacterial effects of edible films and coatings prepared from orange, lemon and pomegranate peels on these bacteria were also investigated with the well agar diffusion technique in the current study. The essential oils (EOs) used in the study were obtained from the fruit peels by the distillation method. To test the antibacterial susceptibilities of essential oils, sterile discs were placed on the surface of the Petri dishes which were inoculated by bacteria. The dishes were incubated at 37 °C for 24 h. At the end of the incubation period, the zone diameters observed around the discs were measured. Florfenicol, flumequine and oxytetracycline were used as control antibiotics in the study. Antibacterial susceptibilities of fruit peels were also determined by broth dilution technique. The Minimum Inhibition Concentration (MIC) values of the fruit peels were found and the lowest concentration where turbidity which was not observed was accepted as MIC for that bacterial species. Carragenean, xanthan, starch and carop were used as matrix in the preparation of edible films and coatings. According to the results of the study, it was found that EO extract prepared from lemon peels was more effective on A. hydrophila, A. caviae and A. allosaccharophila than EO extracts prepared from pomegranate and orange peels in disc diffusion test. Also, it was found that edible films prepared from pomegranate peels had the most antibacterial effect on the three bacterial species.